(3GdeqONQGJ (B:s (3CMcGegG hWQb JchjfgG hGSJKeGQgG aj Gdabg GdESdGej (B/s - (3SGfh, bWH eUWais ((3YeGf(B: s (3OGQ GdfaGFS ddfTQ hGdJhRjY(B, s, 2001)
(3CVhGA Yf GdEONGQ hGdESJKeGQ ef GdefXhQ GdESdGej(B- (3GdEONGQ ef GdefXhQ GdESdGej(B-(3GdESJKeGQ ef GdefXhQ GdESdGej(B- (3WQb Jchjf GdeONQGJ ef GdefXhQ GdESdGej(B- (3GdEfJGL hOhQg aj Jchjf GdeONQGJ(B- (3GdEfaGb hOhQg aj Jchjf GdeONQGJ(B- (3WQb ESJKeGQ GdeONQGJ ef GdefXhQ GdESdGej(B- (3bQGAI aj WQb abgjI dESJKeGQ GdeONQGJ(B- (3bQGAI aj WQb MOjKI dESJKeGQ GdeONQGJs
Keywords: (3GdESJKeGQs; (3GdGfaGbs; (3Gdabg GdGSdGejs